Isolation and Molecular Docking of Cytotoxic Secondary Metabolites from Two Red Sea Sponges of the Genus Diacarnus. Issue 2 (14th January 2021) - Al‐Tarabeen, Mousa; El‐Neketi, Mona; Albohy, Amgad; Müller, Werner Ernst Georg; Rasheed, Mohammed; Ebrahim, Weaam; Proksch, Peter; Ebada, Sherif Saeed
Abstract: Chemical investigation of methanol extracts from two Jordanian marine sponges belonging to genus Diacarnus: D. erythraeanus and D. ardoukobae (family Podospongiidae) afforded a series of norterpene cyclic peroxides namely; muqubilone A (1 ), sigmosceptrellin‐B (2 ), sigmosceptrellin‐B methyl ester (3 ), (+)‐methyl‐2‐epinuapapuanoate (4 ); (−)‐methyl‐2‐epinuapapuanoate (5 ) in addition to a macrolide derivative: latrunculin B (6 ). Chemical structures of isolated compounds were elucidated based on their 1D and 2D NMR and mass spectra as well as by comparison with the literature. All isolated compounds were assessed for their cytotoxic activity against the murine lymphoma (L5178Y) cell line. Among tested compounds, only (2 –4 ) displayed significant cytotoxicity with IC50 values ranging from 1.2 to 6.4 μ M. Molecular docking studies of isolated compounds suggested potential EGFR inhibition and the correlation between docking scores and biological data was strong based on Pearson's correlation coefficient ( r =0.93). Abstract : Two Jordanian marine sponges belonging to genus Diacarnus were chemically investigated yielding five norterpene cyclic peroxides along with one macrolide derivative. In the cytotoxic assay, compounds sigmosceptrellin‐B (2 ), its methyl ester (3 ) and (+)‐methyl‐2‐epinuapapuanoate (4 ) displayed significant cytotoxicity with IC50 values ranging from 1.2 to 6.4 μ M. Molecular docking studies suggested potential EGFR inhibition with a strong correlation between docking scores and biological data based on Pearson's correlation coefficient ( r =0.93).